Growth or stagnation? : a review of Bangladesh's development, 1996. - Centre for Policy Dialogue (Bangladesh) (Dhaka : Centre for Policy Dialogue : University Press Ltd., 1997)
Contributed articles.
Includes bibliographical references.
Keywords: Bangladesh -- Economic policy; Bangladesh -- Economic conditions; Rural poor -- Bangladesh